Is Platelet-Rich Plasma Effective in Enhancing Spinal Fusion? Systematic Overview of Overlapping Meta-Analyses. Issue 2 (March 2022) - Muthu, Sathish; Jeyaraman, Madhan; Ganie, Parvez Ahmad; Khanna, Manish
Study Design: Systematic review. Objectives: We performed this systematic overview on overlapping meta-analyses that analyzed the role of platelet-rich plasma(PRP) in enhancing spinal fusion and identify which study provides the current best evidence on the topic and generate recommendations for the same. Materials and Methods: We conducted independent and duplicate electronic database searches in PubMed, Web of Science, Embase, Cochrane Database of Systematic Reviews, and Database of Abstracts of Reviews of Effects till October-2020 for meta-analyses that analyzed the role of PRP in spinal fusion procedures. Methodological quality assessment was made using Oxford Levels of Evidence, AMSTAR scoring, and AMSTAR 2 grades. We then utilized the Jadad decision algorithm to identify the study with highest quality to represent the current best evidence to generate recommendations. Results: 3 meta-analyses fulfilling the eligibility criteria were included. The AMSTAR scores of included studies varied from 5-8(mean:6.3) and all included studies had critically low reliability in their summary of results due to their methodological flaws according to AMSTAR 2 grades. The current best evidence showed that utilization of PRP was not associated with significant improvement in patient-reported outcomes such as Visual Analog Score for pain compared to the standard fusion procedure. Moreover, PRP was found to be associated with lower fusion rates. Conclusion: Based on this systematic overview, the effectiveness of PRP as a biological agent in augmenting spinal fusion is limited. Current evidence does not support the use of PRP as an adjuvant to enhance spinal fusion.